Fluocinolone acetonide 0.2 µg/day intravitreal implant in non-infectious uveitis affecting the posterior segment: EU expert user panel consensus-based clinical recommendations - Uwe Pleyer; Carlos Pavesio; Elisabetta Miserocchi; Carsten Heinz; Helen Devonport; Víctor Llorenç; Tomás Burke; Vanda Nogueira; Laurent Kodjikian; Bahram Bodaghi (Journal of Ophthalmic Inflammation and Infection)
Abstract Background Non-infectious uveitis affecting the posterior segment of the eye (NIU-PS) is an inflammatory disease, which can significantly impair visual acuity if not adequately treated. Fluocinolone-acetonide sustained-release-0.2 µg/day intravitreal (FAc) implants are indicated for prevention of relapse in recurrent NIU-PS. The aim here was to provide treating clinicians with some consensus-based-recommendations for the clinical management of patients with NIU-PS with 0.2 µg/day FAc implants. Methods A European-clinical-expert-group agreed to develop a consensus report on different issues related to the use of FAc implants in patients with NIU-PS. Results The Clinical-expert-panel provided specific recommendations focusing on clinical presentation (unilateral/bilateral) of the NIU-PS; systemic involvement of NIU-PS and the lens status. Treatment algorithms were developed; one that refers to the management of patients with NIU-PS in clinical practice and another that establishes the best clinical scenarios for the use of FAc implants, both as monotherapy and as adjuvant therapy. Additionally, the Clinical-expert-panel has provided recommendations about the use of the FAc implants in a clinical-setting. The Clinical-expert-panel also considered the safety profile of FAc implants and their possible implications in the daily practice. Conclusions As more clinical experience has been gained using FAc implants, it was necessary to update the clinical recommendations that guide patient management in the clinic. The current consensus document addresses relevant issues related to the use of FAc implants on different types of patients with various etiologies of NIU-PS, and was conducted to standardize approaches to help specialists obtain better clinical outcomes.